PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN BUDAYA KERJA TERHADAP MOTIVASI KERJA KARYAWAN PADA TOKO GROSIR KELUARGA (STUDI KASUS TOKO MUJAHID DAN TOKO SNACK WARIS JAYA) - silvi Wulandari; Raisa Hilia Aini Syifa (LP2M Universitas Perjuangan Tasikmalaya, 2026)
The research was conducted at Mujahid Store and Waris Jaya Snack Store using a quantitative descriptive method approach. The sampling technique applied was saturated sampling, in which the entire population of 46 individuals was assigned as respondents. Data were collected through the distribution of questionnaires using a likert scale, which were subsequently analyzed using the multiple linear regression technique. The findings reveal that situational leadership style had a significant influence on employee work motivation (t = 5.200; sig = 0,000), then work culture also has a significant effect on work motivation (t = 2,133; sig = 0,039). Simultaneously, both variables had a significant effect on work motivation (f = 32,801; sig = 0,000), with a contribution of 58,5%. Based on these results, it can be concluded that situational leadership style and work culture have a significant effect on work motivation.